The biological fate of the polymer nanocarrier material monomethoxy poly(ethylene glycol)-block-poly(d,l-lactic acid) in rat - Xiangjun Meng; Zhi Zhang; Jin Tong; Hui Sun; John Paul Fawcett; Jingkai Gu (Elsevier, 2021)
Monomethoxy poly(ethylene glycol)-block-poly(d,l-lactic acid) (PEG-PLA) is a typical amphiphilic di-block copolymer widely used as a nanoparticle carrier (nanocarrier) in drug delivery. Understanding the in vivo fate of PEG-PLA is required to evaluate its overall safety and promote the development of PEG-PLA-based nanocarrier drug delivery systems. However, acquiring such understanding is limited by the lack of a suitable analytical method for the bioassay of PEG-PLA. In this study, the pharmacokinetics, biodistribution, metabolism and excretion of PEG-PLA were investigated in rat after intravenous administration. The results show that unchanged PEG-PLA is mainly distributed to spleen, liver, and kidney before being eliminated in urine over 48 h mainly (>80%) in the form of its PEG metabolite. Our study provides a clear and comprehensive picture of the in vivo fate of PEG-PLA which we anticipate will facilitate the scientific design and safety evaluation of PEG-PLA-based nanocarrier drug delivery systems and thereby enhance their clinical development.